2015
DOI: 10.1002/adem.201500409
|View full text |Cite
|
Sign up to set email alerts
|

First Cold Spraying of Carbonated Biomimetic Nanocrystalline Apatite on Ti6Al4V: Physical–Chemical, Microstructural, and Preliminary Mechanical Characterizations

Abstract: Carbonated Biomimetic Nanocrystalline Apatite (BNAc) coatings are obtained for the first time by Cold Spray. The coatings are characterized by FTIR, Raman, XRD, and SEM and compared to the powders. No significant chemical and structural changes are detected and the nanostructure features of these very reactive BNAc are preserved in the coating. These results and preliminary mechanical assays show that Cold Spray can produce an operational biomimetic coatings offering a high potential for implants functionaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Some attempts have been performed with ceramic powders on soft substrates such as PEEK and magnesium . The first particles impact and embed into the soft substrates; further impinging particles collide on the previous deposited particles and help them to be deeper embedded, mostly resulting in thin layers with posterior coating build‐up being hardly likely to occur . On the other hand, it is thought on harder substrates that the optimal particle state for a successful substrate attachment is that in which the Hugoniot Elastic Limit (HEL) of the ceramic is reached …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some attempts have been performed with ceramic powders on soft substrates such as PEEK and magnesium . The first particles impact and embed into the soft substrates; further impinging particles collide on the previous deposited particles and help them to be deeper embedded, mostly resulting in thin layers with posterior coating build‐up being hardly likely to occur . On the other hand, it is thought on harder substrates that the optimal particle state for a successful substrate attachment is that in which the Hugoniot Elastic Limit (HEL) of the ceramic is reached …”
Section: Introductionmentioning
confidence: 99%
“…Those studies evaluated the deposition of porous sintered microcrystalline HA powders, showing mechanisms proceeding through pore collapse, fragmentation, and densification as well as grain refinement. However, the fragmentation of crystal grains which proceed by cracking and crushing, do not lead to the build‐up of a coating . On the other hand, the deposition mechanisms of agglomerated nanocrystalline HA powders has been understood by the compaction of nanocrystalline grains within the particle leading to successful build‐up of a coating up to 350 μm …”
Section: Introductionmentioning
confidence: 99%
“…For brittle ceramics, such "cold" deposition process is still questionable, but it was found that rather thick and adhesive coatings could be obtained with specific ceramic powders deposited on metallic, ceramic, or polymeric substrates: e.g., hydroxyapatite (HA) [5]- [7], TiO2 [8]- [10] Y203 [11] or SiC [12]. Dense ceramic powder is not relevant because the breaking of the particles leads to blocky fragments embedded like grit residues in a sand blasted surface.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, cold spray materials are metal materials with high plasticity, such as copper (Yin et al , 2013), aluminum (Huang et al , 2017, 2018a, 2018b), zinc (Chavan et al , 2013), nickel (Bae et al , 2012), titanium (Vidaller et al , 2015) and Fe-based alloys (Spencer and Zhang, 2011). Nowadays, cold spray technology has been widely used in the manufacture of anticorrosive coatings (Huang et al , 2017, 2018a, 2018b; Chavan et al , 2013), functional coatings/material (Hasniyati et al , 2016; Kergourlay et al ,2015; Dardona et al , 2016), additive manufacturing (Astarita et al , 2016).…”
Section: Introductionmentioning
confidence: 99%